Kajian morfologi spermatozoa sapi simmetal di beberapa Balai Inseminasi buatan Indonesia - M.Riyadhi .; R.I. Arifiantini .; B.Purwantara . (Hemera Zoa, 2010)
Morphological abnormality of sperm in semen of males have been associated with sub fertility and sterility for many years. This study to evaluated spermatozoa morphology especially primary abnormality of Simmental bull spermatozoa at several Artificial Insemination centre in Indonesia. One ejaculated were examined from each bull. Total of 70 bulls were tested in this study. One drop of semen was placed on each of 3-4 glass slides, and smears were prepared and air-dried. The spermatozoa were stained with carbolfluchsin-eosin (Williams stained). The types of morphological abnormalities were counted from 500 cells. Result demonstrated that from 70 bulls samples, 48 bulls (68.6%) were indicated low sperm abnormality (10%) were found in 6 bulls (8.57%). The highest type of abnormality found in all samples was pearshape (2.81±0.36%) and lowest were macrocephalus and double head (0.01±0.01%)